2017
DOI: 10.18632/oncotarget.17833
|View full text |Cite
|
Sign up to set email alerts
|

Association between three VEGF polymorphisms and renal cell carcinoma susceptibility: a meta-analysis

Abstract: Several studies have reported an association between vascular endothelial growth factor (VEGF) gene polymorphisms rs2010963, rs3025039 and rs699947 and renal cell carcinoma (RCC). However, the results remain inconclusive and controversial. We therefore conducted a meta-analysis to evaluate this association. Electronic databases were searched for relevant case-control studies up to November 2016. RevMan 5.2 software and STATA version 12.0 were used for statistical analysis in our meta-analysis. Heterogeneity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Similarly to our results Sáenz-López and al [13] reported that -2578C/A, -460T/C, -405C/G, -936C/T VEGF polymorphisms do not appear to exert a significant effect on RCC risk in Spanish population. Regarding VHL gene polymorphisms (rs1642742 and rs779805), numerous studies have examined the association with development and/or prognosis of RCC but with inconclusive results [14,15] (Table 5). It has reported that the existence of G allele at both rs1642742 and rs779805 may play an important role in tumorigenesis of RCC through methylation of CpG island to suppress gene expression [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to our results Sáenz-López and al [13] reported that -2578C/A, -460T/C, -405C/G, -936C/T VEGF polymorphisms do not appear to exert a significant effect on RCC risk in Spanish population. Regarding VHL gene polymorphisms (rs1642742 and rs779805), numerous studies have examined the association with development and/or prognosis of RCC but with inconclusive results [14,15] (Table 5). It has reported that the existence of G allele at both rs1642742 and rs779805 may play an important role in tumorigenesis of RCC through methylation of CpG island to suppress gene expression [15].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding VHL gene polymorphisms (rs1642742 and rs779805), numerous studies have examined the association with development and/or prognosis of RCC but with inconclusive results [14,15] (Table 5). It has reported that the existence of G allele at both rs1642742 and rs779805 may play an important role in tumorigenesis of RCC through methylation of CpG island to suppress gene expression [15]. These discrepancies might depend on ethnicity or the different carcinoma types.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several biomarkers for KIRC that have been detected include von Hippel-Lindau (VHL) [ 8 11 ], vascular endothelial growth factor (VEGF) [ 12 15 ], carbonic anhydrase IX (CAIX) [ 16 18 ], and hypoxia-inducible factor 1 alpha/2 alpha (HIF1a/2a) mutations [ 19 21 ], some of which were able to forecast the medical effectiveness and outcomes. Despite that, there have been scarce studies into the molecular biomarkers of KIRP for the prediction of therapeutic efficacy and prognostication.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF specifically binds to two transmembrane tyrosine kinase receptors (VEGFR) on endothelial cells for transduction of the intracellular signal required for angiogenesis [25]. According to several authors, carriage of the genotype CC / CA of the gene VEGF 2578 C> A is associated with an increase in the synthesis of VEGF-A in plasma and the risk of metastasizing a number of epithelial cancers; In contrast, the variant -2578A allele is associated with a decrease in the transcription of the AP-protease and the synthesis of VEGF-A in tissues [26][27]. A decrease in VEGF-A production may account for the low activity of angiogenesis in tissues, including endometrium, in carriers of the genotype AA / AC of the VEGF 2578 C> A gene [28].…”
Section: Figure 6 Distribution Of Carrier Frequencies Of the -2578a mentioning
confidence: 99%